The Concept of Depression in The Perspective of The Quran - Nurmalia Lusida; Suherman Suherman; Dadang Herdiansyah; Fini Fajrini; Noor Latifah (Indonesian Journal of Islam and Public Health, 2022)
According to the Quran, this study aims to determine (1) the concept of depression in children and adolescents. (2) the causes or reasons for the emergence of depression in children and adolescents. (3) How can the efforts be applied to overcome this depression problem according to the Islamic religion. This research uses quantitative methods through descriptive analysis. The verses in the holy book of the Qur'an are used as perspective samples to be associated with depression problems among adolescents and children. In addition, researchers also look for sources from various literature, from books, journals, and articles related to this study, to be analyzed and developed in narrative form to be studied and understood following Islamic teachings. This research has the result that the concept of depression, according to the perspective of the Qur'an, is an emotional force coupled with a spiritual approach inherent in human psychology in practicing faith in their hearts. The practice of faith is an essential aspect of human life. Without faith, or if the person does not believe, it is feared that he will get a punishment or punishment, which can be illness or other things. In addition, faith is one aspect that guides humans to the right path, corrects a person's wrong behavior, actions, thoughts, or views, and brings them to follow what Allah SWT wills. Depression is a problem that involves a person's psychological and mental life due to the pressure/issues that cause this to happen. This psychological problem can only be treated by a psychologist or psychiatrist formally. This study also shows that depression problems that occur among children and adolescents can be treated and overcome by increasing the practice of faith in everyday life. The practice of faith can be done, among others, by diligently worshiping, praying, drawing closer to Allah, purifying oneself from intentional and unintentional sins, diligently reading the Qur'an, and practicing the holy book in daily personal life to get a sense of security and protection. True from Allah SWT.